2009
DOI: 10.1007/s00436-009-1476-z
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of different fungal structures of Duddingtonia flagrans to the digestive process and predatory ability on larvae of Haemonchus contortus and Strongyloides papillosus in goat feces

Abstract: The dynamics of the passage of conidia, chlamydospores, and mycelia of the fungus Duddingtonia flagrans through the digestive tracts of goats was evaluated. Four groups with five goats each were formed. In the group conidia, each animal received 1 x 10(6) D. flagrans conidia per kilogram of live weight. In the group chlamydospore, each animal received 1 x 10(6) chlamydospores per kilogram of live weight. In the group mycelia, each animal received 1 g of mycelium mass per kilogram of live weight. In the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…The authors, though, did not specify any significant difference (p>0.01) among the tested samples. Differently, Campos et al (2009) observed that the fungus-isolate D. flagrans (CG722) was capable of preying upon and subsequently destroying the L 3 of Strongiloydes pappilosus at the end of their experiments. However, differences in the inter-and intra-specific activities of predatory nematophagous fungi are common and have been observed in experiments with other fungal isolates (Araújo et al 1993).…”
Section: Discussionmentioning
confidence: 93%
“…The authors, though, did not specify any significant difference (p>0.01) among the tested samples. Differently, Campos et al (2009) observed that the fungus-isolate D. flagrans (CG722) was capable of preying upon and subsequently destroying the L 3 of Strongiloydes pappilosus at the end of their experiments. However, differences in the inter-and intra-specific activities of predatory nematophagous fungi are common and have been observed in experiments with other fungal isolates (Araújo et al 1993).…”
Section: Discussionmentioning
confidence: 93%
“…For example, Maciel et al (2009) Chandrawathani et al (1998) studied the effect of A. oligospora on S. papillosus larvae in coprocultures and observed a 99% reduction in the total of larvae recovered when A. oligospora was used at a concentration of 2,000 conidia per gram of feces. Campos et al (2009) evaluated the effect of fungal structures on the number of gastrointestinal larvae of Haemonchus contortus and S. papillosus harvested from fecal goat cultures and noted that D. flagrans survived the passage through the gastrointestinal tract of goats and maintained its predatory activity. Field investigations have proven the effectiveness of nematophagous fungi on nematodes of grazing animals.…”
Section: Resultsmentioning
confidence: 99%
“…The mycelia used in the present experiment had been proven effective in previous studies carried out in Brazil (Alves et al 2003;Assis and Araújo 2003;Silva et al 2009). However, Campos et al (2009) observed that the administration of mycelia to the animals resulted in a short period of efficacy compared to chlamydospores which were very resistant to the passage through the gastrointestinal tract of goats and can maintain their predatory activity for longer periods. However, chlamydospore production requires a longer period of time when compared with the production of mycelia.…”
Section: Discussionmentioning
confidence: 94%